3D-Printable PLA/Mg Composite Filaments for Potential Bone Tissue Engineering Applications - Sumama Nuthana Kalva (17302906) (2023)
Magnesium (Mg) is a promising material for bone tissue engineering applications due to it having similar mechanical properties to bones, biocompatibility, and biodegradability. The primary goal of this study is to investigate the potential of using solvent-casted polylactic acid (PLA) loaded Mg (WE43) composites as filament feedstock for fused deposition modeling (FDM) 3D Printing. Four PLA/Magnesium (WE43) compositions (5, 10, 15, 20 wt%) are synthesized and produced into filaments, then used to print test samples on an FDM 3D printer. Assessments are made on how Mg incorporation affected PLA’s thermal, physicochemical, and printability characteristics. The SEM study of the films shows that the Mg particles are uniformly distributed in all the compositions. The FTIR results indicate that the Mg particles blend well with the polymer matrix and there is no chemical reaction between the PLA and the Mg particles during the blending process. The thermal studies show that the addition of Mg leads to a small increase in the melting peak reaching a maximum of 172.8 °C for 20% Mg samples. However, there are no dramatic variations in the degree of crystallinity among the Mg-loaded samples. The filament cross-section images show that the distribution of Mg particles is uniform up to a concentration of 15% Mg. Beyond that, non-uniform distribution and an increase in pores in the vicinity of the Mg particles is shown to affect their printability. Overall, 5% and 10% Mg composite filaments were printable and have the potential to be used as composite biomaterials for 3D-printed bone implants. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym15112572